A Network for Observing Great Basin Climate Change. (12th March 2013) - Mensing, Scott; Strachan, Scotty; Arnone, Jay; Fenstermaker, Lynn; Biondi, Franco; Devitt, Dale; Johnson, Brittany; Bird, Brian; Fritzinger, Eric
Abstract : The ability to evaluate accurately the response of the environment to climate change ideally involves long‐term continuous in situ measurements of climate and landscape processes. This is the goal of the Nevada Climate‐Ecohydrology Assessment Network (NevCAN), a novel system of permanent monitoring stations located across elevational and latitudinal gradients within the Great Basin hydrographic region (Figure 1). NevCAN was designed, first, to quantify the daily, seasonal, and interannual variability in climate that occurs from basin valleys to mountain tops of the Great Basin in the arid southwest of the United States; second, to relate the temporal patterns of ecohydrologic response to climate occurring within each of the major ecosystems that compose the Great Basin; and, last, to monitor changes in climate that modulate water availability, sequestration of carbon, and conservation of biological diversity.